Gas source localization via behaviour based robot and weighted arithmetic mean / Ahmad Shakaff Ali Yeon. - Ahmad Shakaff Ali Yeon (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main objective of this research is to study, implement and analyze the performance of the implemented algorithms to solve the three main problems of gas source localization. The proposed system focuses on building a reactive mobile robot equipped with gas sensors to find gas plumes and then tracing it to its source. Apart from that, developing a method of declaring the gas plume source is also a focus of this work. This research can be divided into sub-objectives to achieve the stated goal ; to design and develop a mobile robot system for mobile olfaction applications ; to design and implement a reactive multiphase algorithm on the developed mobile robot system and implement a mathematical gas source declaration method ; to analyze the overall performance of the developed mobile robot with its algorithm and the gas source declaration method in an indoor environment.